2016
DOI: 10.1039/c5ra24305j
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient metal salt catalyst for the esterification of biomass derived levulinic acid under microwave irradiation

Abstract: The esterification of the biomass derived platform molecule, levulinic acid, to its alkyl levulinates was carried out over metal salt catalysts under microwave condition, which achieved near-quantitative product yields in a few minutes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 34 publications
0
19
0
1
Order By: Relevance
“…Initially, different metal salt catalysts were selected for the transesterification of soybean oil, which were proved to exhibit different acidic strength in the previous work . The reaction temperature and time for the model reactions were 130 o C and 30 min, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Initially, different metal salt catalysts were selected for the transesterification of soybean oil, which were proved to exhibit different acidic strength in the previous work . The reaction temperature and time for the model reactions were 130 o C and 30 min, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Although significant advances have been made on the development of metal salt catalytic systems for the production of furfural, the reported metal salt catalysts have been almost exclusively based on chloride salts. In our previously reported studies, sulfate salts such as Al 2 (SO 4 ) 3 demonstrated high reactivities that were even better than chloride salts for biomass‐derived alcoholysis/esterification reactions, owing to their good Lewis and Brønsted acidity in methanol solution. These results encouraged us to further investigate their reactivities for the conversion of xylan into furfural in a biphasic solvent system.…”
Section: Introductionmentioning
confidence: 99%
“…Long cycle stability counted for heterogeneous catalyst, while the separation was still proved to be difficult in industry [21]. It is essential to minimize energy consumption for all processes of separation.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%